Spectrum of Diseases among Patients Attending a Breast Clinic at a Tertiary Level Hospital of Bangladesh (BIRDEM Medical Journal, 2019)
Background: Breast problems are a burning health issue for today’s women. Breast clinics provide a competent and complete diagnosis for women with any breast symptoms or problems and give appropriate management of the problem. The aim of this study is to determine the disease spectrum among the patients visiting a breast clinic for assistance.Methods: This was a cross section study of all female patients visiting a breast clinic with breast problems. The study was conducted at BIRDEM General Hospital-2 over a period of 3 years from March 2015 till March 2018. Patients suffering from superficial skin lesions of the breast were excluded. The findings were tabulated and analyzed for frequency of each problem.Results: A total of 1279 patients visited the breast clinic during the period of March 2015 till March 2018. Among them 1204 patients were selected after considering eligibility criteria. The age of the patients ranged from 15 to 80 years. Ten percent of these patients were asymptomatic and attended the clinic for breast screening. Among the symptomatic patients mastalgia was the most common presentation (36.65%) followed by fibrocystic disease (22.26%). Benign Breast lump was seen in 14.96% patients. Ten percent patients presented with breast abscess. Nipple discharge and ductal ectasia was seen in 2.66% patients. Breast cancer was found in 2.33% patients. Other rare entities like milk fistula, giant fibroadenoma were also noted.Conclusion: Breast clinincs provide comprehensive assistance to both benign and malignant breast diseases. Breast cancer is the leading cause of cancer deaths in females. Breast screening ensures early detection of breast cancer. Besides malignant disease benign breast diseases also cause much morbidity to female health. This study shows the spectrum of patients coming with breast complaints to such a breast clinic.Birdem Med J 2019; 9(1): 11-13